Expanding the Sense of Touch Outside the Body - Gonzalez Franco, Mar; Berger, Christopher (Proceedings of the 15th ACM Symposium on Applied Perception, 2018)
Under normal circumstances, our sense of touch is limited to our body. Recent evidence suggests, however, that our perception of touch can also be expanded to objects we are holding when certain tactile illusions are elicited by delivering vibrotactile stimuli in a particular manner. Here, we examined whether an extra-corporeal illusory sense of touch could be elicited using vibrotactile stimuli delivered via two independent handheld controllers while in virtual reality. Our results suggest that under the right conditions, one’s sense of touch in space can be extended outside the body, and even into the empty space that surrounds us. Specifically, we show, in virtual reality, that one’s sense of touch can be extended to a virtual stick one is holding, and also into the empty space between one’s hands. These findings provide a means with which to expand the sense of touch beyond the hands in VR systems using two independent controllers, and also have important implications for our understanding of the human representation of touch.
Best Presentation Award